A comparison of two approaches for representing AAC vocabulary for young children. (October 2015) - Worah, Smita; McNaughton, David; Light, Janice; Benedek-Wood, Elizabeth
Abstract Purpose: Young children with complex communication needs often experience difficulty in using currently available graphic symbol systems as a method of augmentative and alternative communication (AAC). Information on young children's performance with graphic representations based on this population's conceptualizations of these vocabulary items may assist in the development of more effective AAC systems. Method: This study developed Developmentally Appropriate Symbols (DAS) for 10 early emerging vocabulary concepts using procedures designed to address both conceptual and appeal issues for graphic representations for young children. Using a post-test only, between-subjects comparison group design, 40 typically-developing 2.5–3.5-year-old children were randomly assigned to receive a brief training in either of two different types of graphic symbol sets: (a) DAS or (b) Picture Communication Symbols (PCS), a, commercially available graphic symbol system. Result: Results of a two sample independent t-test provide evidence that children in the DAS condition correctly identified more symbols than children trained with the PCS symbols. There was no evidence of a preference between the symbol sets. Conclusion: The results provide support for careful consideration of children's use and understanding of language in developing AAC systems for young children.